Organização do trabalho docente em cursos de graduação na modalidade a distância da UFPB - Mangueira, Caroline Helena Meireles de Medeiros (2019)
The present work has as main topic the Distance Education and its relation with the teaching work on Higher Education Public Institutions. The primary purpose of this study is to analyze elements of intensification in the organization of teaching work of UFPB (an acronym in portuguese for Federal University of Paraíba). To achieve the primary purpose, this work has its focus in the specific objectives, which are: to describe the historical process of institutionalization of the EaD (an acronym in portuguese for Distance Education) in UFPB; to identify the profile of the teaching staff of UFPB’s EaD; to explain the systematization process of organization of the teaching work in the distance-learning courses of UFPB; to establish relations between the EaD legislation and organization of the teaching work. This research is classified as exploratory with a qualitative approach. The individuals studied throughout this work are the professors of the distance-learning courses of Campus I from UFPB. The methodological procedure applied in this project is the documentary research, which aims to analyze the documents related to the regulamentation of the EaD in Brazil and in the UAB (an acronym in portuguese for Universidade Aberta do Brasil) System. The data gathering was made from an interview with an expert of UFPB’s Distance Learning area and a survey with objective and subjective questions to the teaching staff. From the collected data, it was possible to trace the profile of distance education teachers at UFPB. With the qualitative analysis of the answers, we realize that the data indicate the lack of consensus on teachers' perception of labor intensification factors. We also verified the need for initial and continuing training with teachers of Distance Education at UFPB. We conclude that the precariousness in distance education exists and tends to increase if no immediate or short term interventions are made by the institution's administration.